On measuring indebtedness of African countries - Nkamleu, G.B.; Tsafack, R. (2007)
Since the 1950s, export credits have been an important source of finance in most African countries, where they allow more to be invested with less sacrifice of current consumption. This paper provides a framework for comprehensively measuring indebtedness and gives, therefore, a basis for setting objective principles for debt reduction measures. The paper uses a stochastic frontier production function approach and the technical efficiency computation procedure to develop an indebtedness index for 46 African countries. Variations in indebtedness index are explained through a number of institutional, socio-political and geographical factors. The indebtedness index across African countries ranges from a minimum of 3.6% (South Africa) to a maximum of 92% (Zambia), with an average of 69%. Former French colonies exhibited higher indebtedness than former British, Portuguese, or Spanish colonies. Countries in the northern part of the continent are relatively more indebted, while those in the southern part have a lower indebtedness index. Countries which have experienced extended civil wars are generally less indebted. Finally, we measured a significantly higher indebtedness among those countries with dictatorial and corrupt governments.